Mechanosynthesized particles of Galfenol magnetostrictive composition and their polyurethane-bonded magnetoactive composites probed by synchrotron Mossbauer spectroscopy. (2019) - Kiseleva, Tatiana; Zholudev, Sergey; Kabanov, Vladislav; Baulin, Roman; Levin, Eduard; Markov, Gennadiy; Grigoreva, Tatiana; Chumakov, A.; Bessas, D.
Abstract: Galfenol magnetostrictive particles have been mechanochemically synthesized and used as functional component of polyurethane-based composite to achieve magnetoactive elastic response. Synchrotron Mossbauer study was performed on energetic and time scale to reveal local and magnetic structure behavior responsible for the promising composite functionality. Mechanosynthesized particles local heterogeneity as well as particles magnetic domains behavior in external magnetic field were investigated.